Rural Youth and generations. The Experiences of Productive Transformation Processes and Occupational Traditions. A Case Study in the Canton of Naranjo, Alajuela (1980-2008) - Chaves Marín, Adrián (2019)
This is a case study from the canton of Naranjo, Alajuela, between 1980 and 2008 regarding the analysis of national coffee cultivation during peak periods and of crisis. The purpose of this research is to assess the impact of socio-economical processes deriving from the continuity and instability of occupational traditions and their impact on the experiences and construction of identities of the youth of the area. The methodology employed to reach the objective consists of the study of the history of three coexisting generations in Naranjo in order to understand their points of agreement and disagreement. The product of this comparative study will be a set of recommendations for decision making authorities in charge of public policies oriented to inclusive actions for the youth of the area. These recommendations for inclusive actions will also promote citizen engagement, empowerment tools and the search for solutions to problems that affect the segment population.